(3GdahR GdCUZQs - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s ((3YeGO GdOjf eMeO Hf MeOhf GdGUHgGfi s)
(3ChdgG (B:s
(3GdcdGe Ydi GdeSGFd GdKdGK GdJi JTJed Ydi GdYdhe cdgG hHYO aEf gPg GdeSGFd GdKdGK deG cGfJ cGaI eG jfJgi Gdjg GdHMK hfgGjI efG jMQU Ydjg GdYbd s
(3BNQgG (B:s
(3jTJYd HgG Ybhd Ggd GdZadI Edi Gf SCd Ydi TF ef GdMbGFb hgPG eGH dZ eG jLH Cf jJcde ajg Ydi gPg GdeSGFd GdKdGK hHGddg GdJhajb s
(3cJH Hbde NGdj GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1303s
Keywords: (3GdMOjK h GdeUWdMs